A study of bacteria in autopsy room at Chulalongkorn Forensic Center, Faculty of Medicine, Chulalongkorn University. - Thepsitthar , G.; Hoonwijit , U.; Chatsuwan, T.; Nilgate, S. (Chulalongkorn Medical Journal, 2023)
Background : Postmortem culture of forensic cases shows some difficulty in interpretation. Many contaminated organisms may be isolated from the specimens. One of the most important sources of these contaminants may include the environment of the autopsy room. This study of bacteria culture in the autopsy room is therefore made in order to identify colonized bacteria which are able to contaminate in the forensic specimen. Objective : To identify colonized bacteria for assisting in interpretation of postmortem culture. Design : Descriptive study Setting : Department of Forensic Medicine, Faculty of Medicine, Chulalongkorn University. Materials and methods : Three areas of the autopsy room were swabbed by sterile cotton swabs and sent to the microbiology laboratory by Amie’s transport media for 5 days. Isolation and identification of the bacteria were made by Department of Microbiology, Faculty of Medicine, Chulalongkorn University. Result : The culture showed six genera of bacteria which were namely: Bacillus spp., Pseudomonas spp., Klebsiella spp., Enterobacter spp., Escherichia coli and Citrobacter spp.. Conclusion : Bacteria are commonly found in the environment, especially in the hospital, including the autopsy room. The interpretation of these organisms in the specimen must be carefully done. The antemortem history, pathologic findings and multiple samples may be helpful.